2021
DOI: 10.3389/fpsyg.2021.679438
|View full text |Cite
|
Sign up to set email alerts
|

Two Forms of Social Inequality in Students' Socio-Emotional Skills: Do the Levels of Big Five Personality Traits and Their Associations With Academic Achievement Depend on Parental Socioeconomic Status?

Abstract: Some researchers and policymakers advocate a stronger focus on fostering socio-emotional skills in the hope of helping students to succeed academically, especially those who are socially disadvantaged. Others have cautioned that this might increase, rather than reduce, social inequality because personality traits conducive to achievement are themselves unevenly distributed in disfavor of socially disadvantaged students. Our paper contributes to this debate. Analyzing representative, large-scale data on 9,300 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
(156 reference statements)
1
11
1
Order By: Relevance
“…In all our analyses, we controlled for the influence of a set of variables that prior research (e.g., Lechner et al 2021 ) has shown to be linked to both our predictors (i.e., fluid intelligence and conscientiousness) and outcomes (i.e., academic competencies), suggesting that these variables might act as confounders. These variables were participants’ gender (coded as 0 = male, 1 = female) and parental highest occupational prestige (HISEI; Ganzeboom 2010 ) with a possible value range between 11.56 and 88.96.…”
Section: Methodsmentioning
confidence: 99%
“…In all our analyses, we controlled for the influence of a set of variables that prior research (e.g., Lechner et al 2021 ) has shown to be linked to both our predictors (i.e., fluid intelligence and conscientiousness) and outcomes (i.e., academic competencies), suggesting that these variables might act as confounders. These variables were participants’ gender (coded as 0 = male, 1 = female) and parental highest occupational prestige (HISEI; Ganzeboom 2010 ) with a possible value range between 11.56 and 88.96.…”
Section: Methodsmentioning
confidence: 99%
“…An experimental study on 33,000 sixth and seventh graders in Macedonia found that after a year of grit and self-regulation training, students from underprivileged backgrounds made more positive progress in social and emotional skills and academic achievements compared to students from average backgrounds [ 22 ]. This suggests that helping underprivileged-background students improve their social and emotional skills can alleviate the inequality in academic achievements caused by their families’ economic background, thereby promoting educational and social equity [ 11 ]. In recent years, some researchers have conducted studies on how to promote the development of the social and emotional skills of underprivileged-background students, and many believe that the adverse effects of an underprivileged socio-economic background on students can be moderated through the school climate [ 23 , 24 , 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have shown that students’ families have an important influence on their growth [ 6 , 7 , 8 ] and that students from underprivileged family backgrounds tend to achieve poorer development than those from more advantaged family backgrounds [ 9 , 10 , 11 ]. Educational equity is a part of social equity, and educational equity in the modern sense should represent the separation of students’ achievements and their socio-economic background [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result that the higher subjective economic level made learning-related subjective well-being more negatively associated with Machiavellianism, but more positively with gratitude, supported the resource amplification or "Matthew effect" hypothesis which holds that structural characteristics such as a higher socioeconomic status (SES, income is one important indicator of SES; Duncan et al, 2017) and individual characteristics coalesce in producing life outcomes (Walberg and Tsai, 1983) and were consistent with prior studies showing that the relationships between Conscientiousness and academic achievement were higher in higher-vs. lower-SES students (Brandt et al, 2020;Lechner et al, 2021).…”
Section: Discussionmentioning
confidence: 99%